ENSURING THE COMPETITIVENESS OF THE ENTERPRISE UNDER THE CONDITIONS OF DIGITALIZATION: NEW CHALLENGES AND OPPORTUNITIES (Development Service Industry Management, 2023)
In the article, the object of research is the processes of digital transformation of the economy and society, the trends and consequences that accompany them, including the challenges and new opportunities that appear before enterprises in such conditions. Emphasis is placed on management issues and ensuring business competitiveness against the background of comprehensive digitalization of economic relations. The purpose of the study is to identify new challenges and possibilities of digitalization, as well as to substantiate the tools and means of ensuring the competitiveness of enterprises in the environment of digital transformation of the economy. The directions and means of strengthening the competitive positions of enterprises with the use of digital tools, as well as taking into account the challenges and threats of digitalization, have been determined.The applied value of the research results lies in the adaptation of domestic enterprises to management in the new conditions of digitization, information globalization and complex digital transformation of the economy and society.The scientific novelty of the research results lies in the improvement of mechanisms, tools and means of strengthening business competitiveness in the conditions of digitalization, as well as the development of a new methodical approach to the identification of challenges and opportunities of digitalization for business competitiveness.It is shown that in order to ensure the appropriate level of competitiveness of enterprises in the conditions of digitization of their management, it is necessary to work on improving the corporate digital marketing system with a focus on product characteristics that contain sufficient information and communication support, the creation and implementation of information and communication innovative technologies, taking into account of potential consumer requests in the conditions of continuous systemic digital transformation of society. To do this, consumers should be personalized using appropriate tools (large databases, communication platforms), cooperation with leading actors of the local digital communications system.
Keywords: digitization; digital transformation; enterprises; competitiveness; management; new challenges and threats